Evaluation of Metronidazole Resistance of Vaginal Swab Isolates from South African Women Treated for Bacterial Vaginosis - Timo Schwebs; Ann-Katrin Kieninger; Lenka Podpera Tisakova; Vera Oberbauer; Rocío Berdaguer; Andile Mtshali; Gugulethu Mzobe; Anne Rompalo; Adrian Mindel; Marothi Letsoalo; Nigel Garrett; Sinaye Ngcapu; et al. (Antibiotics, 2024)
Background/Objectives: The high recurrence rate of bacterial vaginosis (BV) after antibiotic treatment is at least partially attributed to resistant bacteria. The CAPRISA 083 (CAP083) study investigated the influence of metronidazole (MTZ) treatment on the vaginal microbiome in 56 South African women diagnosed with BV. To explore the etiology of recurrent BV in this cohort, we retrospectively analyzed vaginal swabs collected in CAP083 before and after MTZ treatment. Methods: We isolated over 1200 bacterial strains, including Gardnerella, Lactobacillus, Prevotella, and Fannyhessa, and determined the minimum inhibitory concentration (MIC) of MTZ and the resistance status according to CLSI and EUCAST guidelines. Results: At baseline, 64% (CLSI) of Gardnerella isolates were resistant to MTZ, rising to 80% after MTZ treatment by the 12-week visit. Lactobacillus species consistently exhibited resistance of 100%, while Fannyhessea vaginae maintained resistance rates of 78–91% across visits. Prevotella strains varied, showing two susceptible isolates at baseline and one resistant isolate at the 6-week visit. Susceptible and resistant Gardnerella isolates were often isolated from the same swab, and 70% (CLSI) of participants had at least one resistant Gardnerella strain already at baseline. Sensitive Gardnerella isolates were not a predictor of an MTZ-mediated reduction in Gardnerella abundance. Conclusions: Our data indicate that the 23% cure rate in CAP083 was associated with a combination of a high share of MTZ-resistant bacteria at baseline, a potentially insufficient MTZ dose regimen, and a constantly high average abundance of Gardnerella. Future research should explore novel therapeutic strategies to enhance treatment efficacy and combat antibiotic resistance.